EFEKTIVITAS PROGRAM POLISI HEBAT SEMARANG (LIBAS) DALAM MENANGANI KEJAHATAN DI KOTA SEMARANG - Sahitya Maida Azmi Aruna; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The high crime rate in an area is an important factor in determining the survival of the community. The existence of crime can have a negative impact on all aspects of life and even lead to death. This is because the number of crimes continues to increase, causing the community to lose trust in the authorities responsible for preventing crime. The Semarang City Police, as the main agency responsible for combating crime in Semarang, has finally decided to implement its latest strategy to deal with this situation. Seeing that Semarang is a city with rapid technological development, the Semarang City Police took this opportunity to make a new breakthrough in their services by creating “LIBAS”. However, it turns out that LIBAS has not brought about significant changes. This is because crime in Semarang City has not subsided each year. In fact, several problems have been identified in various aspects of LIBAS, such as server issues, unaddressed reports, unguaranteed user privacy, and a lack of public understanding regarding the use of LIBAS. Therefore, further analysis is needed to determine the effectiveness of the LIBAS program in its efforts to handle crime cases in Semarang City. This study is a descriptive qualitative study using Sutrisno's Program Effectiveness Theory (2007) to describe the effectiveness of the LIBAS program and G. Shabbir Cheema and Dennis A. Rondinelli's Theory of Program Implementation (1983) to identify the inhibiting factors that affect the effectiveness of the LIBAS program. The data collection methods used were interviews, observation, and documentation to obtain primary and secondary data sources. Meanwhile, the qualitative data analysis techniques used were data reduction, data presentation, and conclusion drawing. Finally, data validity was tested using source triangulation and technique triangulation.